La « guerre d’usure » égypto-israélienne, 1968-1970 - Duclos, Louis-Jean (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1979)
The « War of Attrition » constituted one of the crises of the ongoing Arab-Israeli confrontation. From March 8th 1969 Arab revendications for restoration by Israel of the territories lost in 1967 took, under Egyptian direction and the urging of the Palestinian movement, the form of a limited armed conflict. We postulate that the evolution of this crisis depended not only on the capabilities of the belligerents nor on the intervention of the superpowers but also on the objectives of the principal actors. Analysis of these objectives confirms the radical nature of the hostility between Egypt and Israel and the both defensive and restitutory aspect of each country's goals. It emphasizes above all that the object of the crisis was basically the occupied territories dispute and that the cease-fire has left a legacy of heightened disaffection in comparison with the period preceding the crisis. Examination of the behavioral data enables the delimitation of not only the dyadic and polarized configuration of the confrontation but also the latter's context. The search for a purely interactional determination of behaviour leads one to put forward prudently that an increase in lsraeli coercion is related to deescalation while an aggravation of Egyptian belligerence produces the opposite effect. The latter being often preceded in Cairo by the articulation of negative objectives, one could conclude, provisionally, that the « War of Attrition » evolved according to a multivariate open model in which the objectives of Cairo determined the conduct of Israel subject to the intervening Egyptian behavioural variable.